Gamat or Timun Laut? Ossicle shapes of Holothuria (Merthensiothuria) leucospilota and Stichopus horrens for identification - Kamarudin, Kamarul Rahim (2011)
Gamat is a local name for all species of family 3chopodidae. Genera of Stichopus and Thelenota are the two members of family Stichopodidae which can be found in Malaysia’s seawaters e.g. Stichopus horrens Selenka, 1867 and Thelenota anax. Gamat has been exploited for its body fluid extracts i.e. air gamat and lipid extracts i.e. minyak gamat. In line with the development of science and technology, modern-‐formularised gamat-‐based products sold by Malaysia’s companies e.g. Gamat eMas Sdn. Bhd., Nur Af Enterprise, Nutrifes Food & Beverages Industries Sdn. Bhd., and Luxor Network Sdn. Bhd. are also available in the markets. u S. horrens or Gamat Emas has been used as the main ingredient.